The Influence Of Reference Group And Perceived Quality Toward Purchase Decision Of Decorative Cosmetics For Lips Without The Halal Label - Fauziya, Sausan; Lutfi, Ikhwan (‎‎‎TAZKIYA: Journal of Psychology, 2017)
The purpose of this research is to find out the influence of reference group and perceived quality toward purchase decisions of decorative cosmetics for lips without the halal label. The sample amount of 255 female students at Faculty of Psychology UIN Jakarta which were taken with non probability sampling. Data analysis used binary logistic regression analysis technique. The result found that there was significant effect of reference group and perceived quality on purchase decision which was explained in all independent variables was 30,8%, while 69,2% was influenced by external variable of this research. Overall these result indicated that the best predictor of purchase decision of decorative cosmetics for lips without halal label are performance, beauty bloggers, and serviceability. Therefore, for further research is suggested to examine another variables other namely culture, family, age, job, life style, personality, motivation and attitude is recommended for future research. DOI:10.15408/tazkiya.v22i2.8411